The Battle of Stalingrad in the Context of Modern History - M. Y. Myagkov (MGIMO University Press, 2013)
Proceeding 200 days and nights the Battle of Stalingrad became a turning point in the Great Patriotic War of the Soviet people and in all World War II, it turned back, in the western direction movement of the Soviet-German front when Hitler was compelled to recognize that for Germans "possibility of the end of war in the east by means of approach more doesn't exist". After Stalingrad it became clear to the whole world that war against the USSR for a coalition of fascist aggressors is lost. Defeat near Stalingrad allied Germany of armies cracked the fascist block, having forced Italy, Romania, Hungary and Finland actively to look for contacts with the countries of an anti-Hitleriwste coalition for the purpose of a withdrawal from a war. The developed events put an end to calculations on the introduction in war against the USSR to Turkey and Japan, were decisive incentive of growth of a resistance movement in Europe and Asia. The western allies of the USSR intensified preparation for opening of the second anti-Hitlerite front in Europe. U.S. President F.Ruzvelt called battle near Stalingrad epic. Later it sent the diploma of the following contents: "On behalf of the people of the United States of America I hand over this diploma to the city of Stalingrad to note our admiration of his valorous defenders … Their nice victory stopped a wave of invasion and became a turning point of war of the allied nations against aggression forces".